2016
DOI: 10.1177/0261927x15614343
|View full text |Cite
|
Sign up to set email alerts
|

Is the Marker the Message? The Role of Some Scalar Adverbs in the Processing of a Public Health Appeal and Its Effectiveness

Abstract: In this study, we argue that studies in persuasive communication have been undertaken until now without considering enough the main ideas of pragmatics as regards the communication process and the use of language. In particular, we suggest that in this area of research, it could be relevant to ponder the processes involved in the message processing by taking into account the “inferential” and “intentionalist” paradigm of communication. To support our claim, we propose an experimental study designed in the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Barry et al (2018) also demonstrated that a small change in the name of drug intervention sites could enhance public support for harm reduction interventions to control the ongoing opioid epidemic. Coppola and Girandola's (2016) experimental study proved that adopting scalar adverbs in epidemiological information messages can facilitate the readers' cognitive processing of the designed communicative intentions in a preventive program. Other scholars have focused on how infectious diseases such as SARS, Ebola, and the flu are socially constructed in newspapers by deploying linguistic resources, such as conceptual metaphors (Baehr, 2006;Chung, 2011;Dobric & Weder, 2016;Wallis & Nerlich, 2005), "othering" mechanism (Washer, 2004), lexis choice, foci of attention, and tone of writing (Chung, 2011), demonstrating that such linguistic choices often reflect ideological concerns, as well as social and cultural values.…”
Section: Introductionmentioning
confidence: 91%
“…Barry et al (2018) also demonstrated that a small change in the name of drug intervention sites could enhance public support for harm reduction interventions to control the ongoing opioid epidemic. Coppola and Girandola's (2016) experimental study proved that adopting scalar adverbs in epidemiological information messages can facilitate the readers' cognitive processing of the designed communicative intentions in a preventive program. Other scholars have focused on how infectious diseases such as SARS, Ebola, and the flu are socially constructed in newspapers by deploying linguistic resources, such as conceptual metaphors (Baehr, 2006;Chung, 2011;Dobric & Weder, 2016;Wallis & Nerlich, 2005), "othering" mechanism (Washer, 2004), lexis choice, foci of attention, and tone of writing (Chung, 2011), demonstrating that such linguistic choices often reflect ideological concerns, as well as social and cultural values.…”
Section: Introductionmentioning
confidence: 91%